Object-oriented design knowledge principles, heuristics, and best practices - Garzas, Javier 1975-; Piattini, Mario 1966-; Gale Group (Hershey, Penn. Idea Group Publishing, 2007)
"The software engineering community has advanced greatly in recent years and we currently have numerous defined items of knowledge, such as standards, methodologies, methods, metrics, techniques, languages, patterns, knowledge related to processes, concepts, etc.The main objective of this book is to give a unified and global vision about Micro-Architectural Design Knowledge, analyzing the main techniques, experiences and methods"--Provided by publisher.
Preface -- Object-oriented design knowledge -- The object-oriented design knowledge ontology -- Using linguistic patterns to model interactions -- A framework based on design patterns: implementing UML association, aggregation and composition relationships in the context of model driven code generation -- Design patterns as laws of quality -- Automatic verification of OOD pattern applications -- From bad smells to refactoring: metrics smoothing the way -- Heuristics and metrics for OO refactoring: A consolidation and appraisal of current issues -- A survey of object oriented design quality improvement -- A catalog of design rules for micro-architecture -- About the authors -- Index.
Electronic reproduction.
Keywords: Object-oriented methods (Computer science); Object-oriented programming (Computer science); Electronic books